Support and compliance with 20 mph speed limits in Great Britain. (May 2015) - Tapp, Alan; Nancarrow, Clive; Davis, Adrian
Highlights: Lack of compliance with 20 mph limits in GB and 30 kph limits across Europe by drivers is a cause for concern. Data was collected to examine support–opposition and compliance–non-compliance amongst the GB population. Four categories of driver according to support/opposition and compliance/non-compliance were examined in detail. Results indicated that self-enhancement bias, social contagion and habitual/inattentive driving were important factors in explaining non-compliance. Pro-active behaviour change strategies are required to create higher compliance levels. Abstract: There are a number of challenges relating to both the support of and compliance with speed limits. The introduction of 20 mph limits in Great Britain is no exception: the recent rise in the deployment of these limits in urban settings has created a need to understand these issues in more depth. This paper reports a study undertaken by the authors that used a population wide survey of GB drivers to explore how support and compliance were interlinked. Whilst as expected many supporters said they would comply with the limits, and many opponents might not comply, more surprisingly it was also found that some supporters claimed not to comply, while some opponents of 20 mph limits were compliers. Explanations included the strong likelihood of strong moral adherence to not breaking laws amongst opponent–compliers, and self-enhancement bias amongst supporter–non-compliers. This paper explores the incidence of these effects and their implications in detail.